2022
DOI: 10.3390/w14152301
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic Dye Degradation and Bio-Insights of Honey-Produced α-Fe2O3 Nanoparticles

Abstract: Iron oxide nanoparticles are produced using simple auto combustion methods with honey as a metal-stabilizing and -reducing agent. Herein, α-Fe2O3 nanoparticles are produced using an iron nitrate precursor. These prepared samples are analyzed by an X-ray diffractometer (XRD), FTIR spectroscopy, UV-DRS, and a field-emission scanning electron microscope (FESEM) combined with energy-dispersive spectroscopy and a vibrating sample magnetometer (VSM). The XRD results confirm a rhombohedral structure with an R3c¯ spac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 64 publications
2
7
0
Order By: Relevance
“…The SEM images of the present study revealed that the precursor (honey) was stabilizing the surface of nanoparticles by selectively slowing their growth rate and stopping particle aggregation. This result can be correlated with a previous similar study [ 23 ]. Another study demonstrated that the nature of Fe 2 O 3 -NPs was not uniform and that they were present mostly in the form of large, agglomerated groups.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The SEM images of the present study revealed that the precursor (honey) was stabilizing the surface of nanoparticles by selectively slowing their growth rate and stopping particle aggregation. This result can be correlated with a previous similar study [ 23 ]. Another study demonstrated that the nature of Fe 2 O 3 -NPs was not uniform and that they were present mostly in the form of large, agglomerated groups.…”
Section: Discussionsupporting
confidence: 93%
“…Recently, researchers reported significant in vitro antibacterial potential of honey-loaded Fe 2 O 3 nanoparticles against P. aeruginosa , B. subtilis , S. aureus , E. coli , Penicillium spp., and Aspergillus spp. [ 23 ]. Another study reported the successful synthesis of Fe 2 O 3 -NPs from Oscillatoria limnetica .…”
Section: Introductionmentioning
confidence: 99%
“…Biological sources have been used for progress of ecological and consistent methodology for the synthesis of various nanomaterials [1]. The interaction of inorganic nanoparticles with biological structures is one of the most exciting areas of research in the modern field of nanotechnology [2][3][4]. Nanoparticles are usually the size of 1 to 100 nm and exhibit different characteristics based on their smaller size, distribution, and morphology compared with bulk materials of the original sources [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…The cobalt ferrite-associated nanoparticles revealed better catalytic activity in UV light irradiation due to OH radical formation [ 50 , 51 , 52 , 53 ]. The pure cobalt ferrite nanoparticles under sunlight illumination exhibited superior degradation performance against various dyes [ 51 , 52 , 53 , 54 , 55 ]. The different dopants against the cobalt ferrites induced higher surface area and extended e–h pair recombination, increasing the degradation potential against toxic dye and organic pollutants [ 53 , 54 , 55 , 56 , 57 ].…”
Section: Resultsmentioning
confidence: 99%
“…The pure cobalt ferrite nanoparticles under sunlight illumination exhibited superior degradation performance against various dyes [ 51 , 52 , 53 , 54 , 55 ]. The different dopants against the cobalt ferrites induced higher surface area and extended e–h pair recombination, increasing the degradation potential against toxic dye and organic pollutants [ 53 , 54 , 55 , 56 , 57 ]. The present work was carried out by visible light irradiation, narrow bandgap, lowset crystallite sizes, and spherically-shaped nanostructure conditions.…”
Section: Resultsmentioning
confidence: 99%